Autoinflammatory Keratinization Disease With Hepatitis and Autism Reveals Roles for JAK1 Kinase Hyperactivity in Autoinflammation - Takeichi, Takuya; Lee, John Y. W.; Okuno, Yusuke; Miyasaka, Yuki; Murase, Yuya; Yoshikawa, Takenori; Tanahashi, Kana; Nishida, Emi; Okamoto, Tatsuya; Ito, Komei; Muro, Yoshinao; Sugiura, Kazumitsu; et al. (Frontiers in Immunology, 2022)
Heterozygous mutations in JAK1 which result in JAK-STAT hyperactivity have been implicated in an autosomal dominant disorder that features multi-organ immune dysregulation. This study identifies another previously unreported heterozygous missense JAK1 mutation, H596D, in an individual with a unique autoinflammatory keratinization disease associated with early-onset liver dysfunction and autism. Using CRISPR-Cas9 gene targeting, we generated mice with an identical Jak1 knock-in missense mutation (Jak1KI mice) that recapitulated key aspects of the human phenotype. RNA sequencing of samples isolated from the Jak1KI mice revealed the upregulation of genes associated with the hyperactivation of tyrosine kinases and NF-B signaling. Interestingly, there was a strong correlation between genes downregulated in Jak1KI mice and those downregulated in the brain of model mice with 22q11.2 deletion syndrome that showed cognitive and behavioral deficits, such as autism spectrum disorders. Our findings expand the phenotypic spectrum of JAK1-associated disease and underscore how JAK1 dysfunction contributes to this autoinflammatory disorder.